2015
DOI: 10.1007/s10509-015-2607-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of emergent universe in brane scenario as a consequence of particle creation

Abstract: Here we formulate scenario of emergent universe from particle creation mechanism in spatially flat braneworld models. We consider an isotropic and homogeneous universe in Braneworld cosmology and universe is considered as a non-equilibrium thermodynamical system with dissipation due to particle creation mechanism. Assuming the particle creation rate as a function of the Hubble parameter, we formulate emergent scenario in RS2 and DGP models of Braneworld.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In [155], the universe is considered as a nonequilibrium thermodynamical system with dissipative phenomena due to particle creation mechanism and it is shown that the EU scenario is a consequence of particle creation process. Work along this line has been carried out in the context of brane world scenarios [156] and inhomogeneous spacetimes [157]. Another possibility has been recently reported in the context of two measure theories (TMT) where the scale invariance is spontaneously broken due to the intrinsic features of the TMT dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In [155], the universe is considered as a nonequilibrium thermodynamical system with dissipative phenomena due to particle creation mechanism and it is shown that the EU scenario is a consequence of particle creation process. Work along this line has been carried out in the context of brane world scenarios [156] and inhomogeneous spacetimes [157]. Another possibility has been recently reported in the context of two measure theories (TMT) where the scale invariance is spontaneously broken due to the intrinsic features of the TMT dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We consider an open thermodynamical system where the number of fluid particles (N) is not conserved [57]. If we assume that there is a transformation of gravitational energy into matter-energy due to random fluctuation in curvature resulting in an additional number of particles dN, then there is an increase in the number of particles from N to N +dN, which give rise to negative supplementary pressure with the thermodynamic pressure.…”
Section: Field Equations and Solutionsmentioning
confidence: 99%
“…To fulfil our goal, here in this paper, we use the parameterization of Γ [60,61,62,63,64,65,66,67,68] as Γ = 3nHη, which a source term indicating the production (Γ > 0) of particles and annihilation (Γ < 0) of the particles, n refers to the particle number density and H is the Hubble parameter (HP). The constant η ∈ [0, 1].…”
Section: Field Equations and Solutionsmentioning
confidence: 99%